Taurodontism in association with supernumerary teeth - (:unkn) unknown (My University, 1999)
The dental, radiological, genetic and dermatoglyphic findings of an additional patient with taurodontism in association with supernumerary teeth were presented and the findings of the patient were compared with those in the literature.
Keywords: Adult; Humans; Male; Maxilla; Dental Pulp Cavity; Mandible; Molar; Pedigree; Dermatoglyphics; Tooth, Supernumerary; Tooth Abnormalities; Tooth, Impacted